An embedded mixed methods investigation of factors associated with the quality of mental health care in the Kingdom of Saudi Arabia (KSA): a structure, process and outcome evaluation - Al Mousa, Yaqoub (2018)
Background: Quality of care (QoC) is the essential determinant of service provision improvement for service users in mental health settings. However, there is a lack of research investigating the factors associated with the quality of mental health care and their relationship to service user outcomes, particularly in Saudi Arabia. This is despite the high priority given to QoC in mental health care in the Kingdom of Saudi Arabia’s (KSA) national health strategy.